Regulation between personality traits: individual social tendencies modulate whether boldness and leadership are correlated. Issue 1880 (13th June 2018) - Bevan, Peggy A.; Gosetto, Isabella; Jenkins, Eliza R.; Barnes, Isobel; Ioannou, Christos C.
Abstract : Although consistent behavioural differences between individuals (i.e. personality variation) are now well established in animals, these differences are not always expressed when individuals interact in social groups. This can be key in important social dynamics such as leadership, which is often positively related to personality traits such as boldness. Individuals consistently differ in how social they are (their sociability), so if other axes of personality variation, such as boldness, can be suppressed during social interactions, this suppression should be stronger in more sociable individuals. We measured boldness (latency to leave a refuge when alone) and sociability (time spent with a conspecific) in three-spined sticklebacks ( Gasterosteus aculeatus ) and tested the boldness–leadership association in pairs of these fish. Both boldness and sociability were repeatable, but were not correlated. When splitting the data between the 50% most sociable and 50% less sociable fish, boldness was more strongly associated with leadership in less rather than more sociable individuals. This is consistent with more sociable fish conforming to their partner's behaviour due to their greater social tendency. One axis of personality variation (sociability) can thus modulate the relationship between others (boldness and leadership), with potential implications for selection on personality variation in social animals.